Five Topics Health Care Simulation Can Address to Improve Patient Safety: Results From a Consensus Process. Issue 2 (June 2019) - Sollid, Stephen J.M.; Dieckman, Peter; Aase, Karina; Søreide, Eldar; Ringsted, Charlotte; Østergaard, Doris
Abstract : Objectives: There is little knowledge about which elements of health care simulation are most effective in improving patient safety. When empirical evidence is lacking, a consensus statement can help define priorities in, for example, education and research. A consensus process was therefore initiated to define priorities in health care simulation that contribute the most to improve patient safety. Methods: An international group of experts took part in a 4-stage consensus process based on a modified nominal group technique. Stages 1 to 3 were based on electronic communication; stage 4 was a 2-day consensus meeting at the Utstein Abbey in Norway. The goals of stage 4 were to agree on the top 5 topics in health care simulation that contribute the most to patient safety, identify the patient safety problems they relate to, and suggest solutions with implementation strategies for these problems. Results: The expert group agreed on the following topics: technical skills, nontechnical skills, system probing, assessment, and effectiveness. For each topic, 5 patient safety problems were suggested that each topic might contribute to solve. Solutions to these problems and implementation strategies for these solutions were identified for technical skills, nontechnical skills, and system probing. In the case of assessment and effectiveness, the expert group found it difficult to suggest solutions and implementation strategies mainly because of lacking consensus on metrics and methodology. Conclusions: The expert group recommends that the 5 topics identified in this consensus process should be the main focus when health care simulation is implemented in patient safety curricula.